Cost effectiveness analysis of neonatal extracorporeal membrane oxygenation based on four year results from the UK Collaborative ECMO Trial. Issue 3 (21st April 2004) - Petrou, S; Edwards, L
Abstract : Objective: To assess the cost effectiveness of extracorporeal membrane oxygenation (ECMO) for mature newborn infants with severe respiratory failure over a four year time span. Design: Cost effectiveness analysis based on a randomised controlled trial in which infants were individually allocated to ECMO (intervention) or conventional management (control) and then followed up to 4 years of age. Setting: Infants were recruited from 55 approved recruiting hospitals throughout the United Kingdom. Infants allocated to ECMO were transferred to one of five specialist regional centres. Follow up of surviving infants was performed in the community. Subjects: A total of 185 mature (gestational age at birth ⩾ 35 weeks, birth weight ⩾ 2000 g) newborn infants with severe respiratory failure (oxygenation index ⩾ 40). Main outcome measures: Incremental cost per additional life year gained; incremental cost per additional disability-free life year gained. Results: Over four years, the policy of neonatal ECMO was effective at reducing known death or severe disability (relative risk = 0.64; 95% confidence interval 0.47 to 0.86; p = 0.004). After adjustment for censoring and discounting at 6%, the mean additional health service cost of neonatal ECMO was £17 367 (95% confidence interval £12 072 to £22 224) per infant (£UK, 2001 prices). Over four years, the incremental cost of neonatal ECMO was £16 707 (£9828 to £37 924) per life year gained and £24 775 (£13 106 to £69 690) per disability-free life year gained. These results remained robust after variations in the values of key variables performed as part of a sensitivity analysis. Conclusions: The study provides rigorous evidence of the cost effectiveness of ECMO at four years for mature infants with severe respiratory failure.